The net beneath us - Dunbar, Carol, 1970- (Forge, 2022)
"He promised her he would never let go. She's willing to risk everything to hold on. In the aftermath of her husband's logging accident, Elsa has more questions than answers about how to carry on while caring for their two small children in the unfinished house he was building for them in the woods of rural Wisconsin. To cope with the challenges of winter and the near-daily miscommunications from her in-laws, she forges her own relationship with the land, learning from and taking comfort in the trees her husband had so loved. If she wants to stay in their home, she must discover her own capabilities, and accept help from the people and places she least expects. Dunbar, drawing from her own lived experiences, vividly describes the wonder and harshness of life off the grid. Told over the course of a year, The Net Beneath Us is a lyrical exploration of loss, marriage, parenthood, and self-reliance; a tale of how the natural world-without and within us-offers us healing, if we can learn where to look"--